PENGARUH METODE WEBQUAL 4.0 TERHADAP KEPUASAN PENGGUNA WEBSITE POLITEKNIK NEGERI SRIWIJAYA - Agnes Manik; Irma Salamah; Eka Susanti (Jurnal Elektro dan Telekomunikasi Terapan (e-Journal), 2017)
Website is one form of mass media that published through internet ne twork that can be accessed wherever and whenever. To be able to get a quality website must be done. By measuring the quality of a website, it can be known the user‘s perception of the website. In this study using WebQual method that has been modofied with the addition the dimension of user satisfactionwith the three main dimensions of WebQual 4.0 usability, information, service interaction. This research was conducted in the environment of State Polytechnic of Sriwijaya. This research was conducted by using questionnaire. The population of this research is State Polytechnic of Sriwijaya collegers. The result obtained in this study is the development of a better website, it is found that the quality of information and quality of usability affects positive on user satisfaction. Quality of service interaction affects a negative on the usersatisfaction of State Polytechnic of Sriwijaya user.